DIGITAL LIBRARIES AND PERSONALISED LEARNING EXPERIENCES OF FINAL YEAR ECONOMICS EDUCATION STUDENTS IN PUBLIC UNIVERSITIES IN LAGOS STATE, NIGERIA - Mohammed, Abidat Oluwashola; Abiodun-Asanre, Oluwaseun Adeola (Faculty of Administrative Science, Universitas Brawijaya, 2023)
This study examined the influence of educational tools in digital libraries on the personalized learning experiences of final year economics education students in public universities in Lagos State, Nigeria. A descriptive research design was employed, with the use of questionnaire tagged Digital Libraries and Personalized Learning Experiences of Students Questionnaire (DLPLESQ) as instrument of data collection. A total of 212 final year economics education students were selected for the study using snowball sampling technique. Descriptive statistics such as frequency distribution, percentage, mean, and standard deviation were used to provide answers to research questions. Additionally, inferential statistics in form of regression analysis was used to test the relevant hypothesis. The findings revealed that digital library tools have a significant positive impact on students' personalized learning experiences of students ( = 2.002; P<0.05). The study also demonstrated that that final year Economics education students are “Not Aware” of the resources in digital libraries in public universities in Lagos State Nigeria. Out of the 13 digital library resources listed, sampled students seem to be “Aware” of only three resources which are “Google Scholar”, “Oxford Academic” and “Research4life”. Furthermore, the study showed that final year Economics education students make use of the digital library resources “Monthly”. Based on these findings, the study recommended strategies to enhance the utilization of digital libraries, such as improving access to devices and internet connectivity, providing training programs to enhance digital literacy skills, and integrating digital library resources into the economics education curriculum.